The Conditions of Opal Formation within the NorthMutnovskaya Volcanic Zone of Kamchatka - O. M. Topchieva; V. A. Petrovsky; M. A. Nazarova; V. M. Chubarov; A. E. Sukharev (Вестник Пермского университета. Геология, 2017)
The characteristics of formation of the opal mineralization in the host rock within Mutnovskaya volcanic zone were studied. The type of metasomatic rock alteration and its consecutive order were established. The results of study allowed identifying the mineral inclusions in opals, which was linked to the metalliferousness of the Mutnovsky hydrothermal system. Probable mechanism of opals formation within the North Mutnovskaya zone is considered, and its characteristics are compared to those from the opal field Raduzhnoye, Primorye.